Outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator and preparation method thereof

By adopting foam copper composite high-entropy ceramic photothermal freshwater evaporator, the problem of low water evaporation efficiency in the prior art is solved, and efficient water evaporation effect is achieved, which is suitable for outdoor applications.

CN116253387BActive Publication Date: 2025-03-21HUBEI UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310155511.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2025-03-21
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

The existing photothermal water evaporation technology has low water evaporation efficiency in outdoor applications, and the interaction process between high-entropy ceramics and sunlight has not been fully studied.

Method used

A foamed copper composite high-entropy ceramic photothermal freshwater evaporator is used to mix cobalt nitrate hexahydrate, ferric nitrate nitrate hexahydrate, nickel nitrate hexahydrate, chromium nitrate hexahydrate, manganese nitrate hexahydrate and cetyl trimethyl ammonium bromide with urea, and a high-entropy ceramic is formed through hydrothermal reaction and heat treatment, and then combined with copper foam is used to prepare a photothermal freshwater evaporator with high water evaporation efficiency.

Benefits of technology

The water evaporation efficiency at 1KW/m2 solar intensity is achieved at 1.20~1.28kg·m-2·h-1, which significantly improves the water evaporation efficiency and is suitable for outdoor sports and survival.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, comprising the following steps: S1, adding cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate hexahydrate, and hexadecyltrimethylammonium bromide to deionized water, mixing evenly, then adding urea, and stirring to obtain a mixed solution; S2, subjecting the mixed solution to a hydrothermal reaction, centrifuging, washing, and drying to obtain a precursor powder; S3, subjecting the precursor powder to a heat treatment to obtain a high entropy ceramic; S4, adding high entropy ceramics and aluminum phosphate to deionized water, ultrasonically dispersing to obtain a suspension, placing copper foam in the suspension, and drying after immersion to obtain an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator. The invention has a simple preparation process and is easy to mass produce; the prepared photothermal fresh water evaporator has a high water evaporation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photothermal fresh water evaporation, and specifically refers to an outdoor foam copper composite high-entropy ceramic photothermal fresh water evaporator and a preparation method thereof. Background Art

[0002] How to obtain drinkable fresh water during outdoor sports and field operations has always been a concern. Solar Steam Generation, as the most direct solar energy-fresh water conversion technology, is currently a hot research topic. Its principle is mainly to use a porous photothermal evaporator to absorb solar energy and convert it into heat energy to achieve efficient evaporation of water vapor. As the core working unit of the Solar Steam Generation system, the structure and performance of the photothermal evaporator also directly determine the fresh water evaporation efficiency. In recent years, most of the research on photothermal evaporators at home and abroad has focused on the development of photothermal material systems and the construction of device structures. The photothermal material systems involved include plasmons, narrow bandgap semiconductors and porous carbon materials, such as the gold nanoparticle film photothermal evaporator reported in the literature (Small, 2014, 10 (16): 3234-3239.), copper oxide nanosheet film photothermal evaporator (Journal of the American Chemical Society, 2019, 141 (47): 18754-18758), wood residual carbon photothermal evaporator (Acs Applied Materials & Interfaces, 2017, 9 (17): 15052.) and the carbonized rice husk foam and graphene foam evaporators disclosed in patent technologies CN201811314211.7 and CN 201811313935.X. High-entropy ceramics are a new type of ceramic material that is currently being widely studied. They are mainly formed by the solid solution of 5 or more oxides. Due to their special thermodynamic high-entropy effect and the comprehensive "cocktail" effect of multi-component characteristics, they show great application prospects in the fields of electricity and magnetism. However, current research has not fully considered the interaction process between high-entropy ceramics and sunlight, especially the absorption and utilization of visible and near-infrared light, and there are no reports on the technology of using high-entropy ceramics as photothermal materials. Summary of the invention

[0003] The purpose of the present invention is to solve the shortcomings of the above-mentioned background technology and provide a method for preparing an outdoor copper foam composite high-entropy ceramic photothermal fresh water evaporator. The method has a simple preparation process and is easy for large-scale production, and the prepared photothermal fresh water evaporator has high water evaporation efficiency.

[0004] The technical solution of the present invention is: a method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, characterized in that it comprises the following steps:

[0005] S1. Add cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate hexahydrate, and hexadecyltrimethylammonium bromide into deionized water, mix well, then add urea, and stir to obtain a mixed solution;

[0006] S2, placing the mixed solution prepared in step S1 into a polytetrafluoroethylene-lined stainless steel hydrothermal autoclave, performing a hydrothermal reaction at 140-160° C., and obtaining a precursor powder by centrifugation, washing, and drying;

[0007] S3, heat treating the precursor powder prepared in step S2 at 900-1000° C. in an air atmosphere to obtain a high entropy ceramic;

[0008] S4. Add the high entropy ceramic and aluminum phosphate prepared in step S3 into deionized water, obtain a suspension after ultrasonic dispersion, place the foam copper in the suspension, immerse for 10 to 20 minutes, take out, and dry to obtain an outdoor foam copper composite high entropy ceramic photothermal fresh water evaporator.

[0009] Preferably, in step S1, the mass ratio of cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate hexahydrate, hexadecyltrimethylammonium bromide, deionized water, and urea is (1.2-1.6):(0.4-0.6):(0.6-0.8):(0.7-0.8):(1.3-1.5):(3.0-3.2):100:(2.0-2.5).

[0010] Preferably, in step S1, stirring is performed for 20 to 30 minutes to obtain a mixed solution.

[0011] Preferably, in step S2, the hydrothermal reaction time is 4 to 6 hours.

[0012] Preferably, in step S3, the heat treatment time is 2 to 3 hours.

[0013] Preferably, in step S4, the mass ratio of high entropy ceramic, aluminum phosphate, deionized water and foamed copper is (5-10):(3-5):100:(10-20).

[0014] Preferably, in step S4, the ultrasonic dispersion time is 20 to 30 minutes.

[0015] Preferably, in step S4, the thickness of the copper foam is 5 to 10 mm, and the pore size is 20 to 60 μm.

[0016] The present invention also provides an outdoor copper foam composite high-entropy ceramic photothermal fresh water evaporator, which is prepared by the preparation method of the outdoor copper foam composite high-entropy ceramic photothermal fresh water evaporator described in any one of the above items.

[0017] In the above scheme:

[0018] In step S1, the purpose of preparing a mixed solution of cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate hexahydrate, hexadecyltrimethylammonium bromide, urea and deionized water is to provide a metal source, a dispersant, a precipitant and a colloidal template. The five metal sources are used to reduce the mixing enthalpy of the reaction and increase the mixing entropy of the reaction. Urea as a dispersant and precipitant can promote the formation of materials. Hexadecyltrimethylammonium bromide as a surfactant is used to control the size and shape of the material.

[0019] In step S2, the principle of the hydrothermal reaction of the mixed solution is that urea is first hydrolyzed in the solution to produce hydroxyl and carbonate, and then reacts with the five metal salts to form hydroxycarbonate and carbonate.

[0020] In step S3, the principle of heat treatment of the precursor powder is to heat treat hydroxycarbonate and carbonate to form high entropy ceramic powder.

[0021] The beneficial effects of the present invention are:

[0022] (1) Since the preparation process of the present invention only includes easy-to-implement technologies such as stirring, drying, hydrothermal treatment, air heat treatment and impregnation, the requirements for equipment and process control are low, so the preparation process is simple and conducive to large-scale production.

[0023] (2) The main photothermal medium material used in the present invention is high entropy ceramic, which has a wide light absorption range, high light absorption rate and excellent photothermal conversion efficiency; at the same time, the foam copper used in the present invention also has a developed three-dimensional porous structure with a pore size of 20 to 60 μm, which can greatly promote the rapid transport of water vapor in the system and improve the water evaporation efficiency. The prepared outdoor foam copper composite high entropy ceramic photothermal fresh water evaporator has a power of 1KW / m 2 The water evaporation efficiency under sunlight intensity is 1.20-1.28 kg·m -2 ·h -1 Therefore, the outdoor copper foam composite high-entropy ceramic photothermal fresh water evaporator prepared by the present invention has a high water evaporation efficiency.

[0024] Therefore, the preparation process of the present invention is simple and easy to mass produce; the prepared photothermal fresh water evaporator has high water evaporation efficiency and is suitable for various outdoor sports and outdoor survival. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the following examples further describe the present invention in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The following specific examples further describe the present invention in detail. The drugs used in the examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods in the art unless otherwise specified.

[0026] Example 1

[0027] This embodiment provides a method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, comprising the following steps:

[0028] S1. Weigh 1.2 parts by mass of cobalt nitrate hexahydrate, 0.4 parts by mass of iron nitrate nonahydrate, 0.6 parts by mass of nickel nitrate hexahydrate, 0.7 parts by mass of chromium nitrate nonahydrate, 1.3 parts by mass of manganese nitrate hexahydrate and 3.0 parts by mass of hexadecyltrimethylammonium bromide, add them to 100 parts by mass of deionized water, mix well, then add 2.0 parts by mass of urea, stir for 20 minutes, and obtain a mixed solution;

[0029] S2, placing the mixed solution into a polytetrafluoroethylene-lined stainless steel hydrothermal autoclave, hydrothermally reacting at 140° C. for 4 h, and obtaining a precursor powder by centrifugation, washing, and drying;

[0030] S3, heat treating the prepared precursor powder at 900° C. in an air atmosphere for 2 h to obtain a high entropy ceramic;

[0031] S4. Weigh 5 parts by mass of high-entropy ceramics and 3 parts by mass of aluminum phosphate, add them to 100 parts by mass of deionized water, and ultrasonically disperse them for 20 minutes to obtain a suspension; take 10 parts by mass of foam copper and place them in the suspension, immerse them for 10 minutes, take them out, and dry them at 60°C for 12 hours to prepare an outdoor foam copper composite high-entropy ceramic photothermal fresh water evaporator.

[0032] In this embodiment, the thickness of the copper foam is 5 mm and the pore diameter is 20 μm.

[0033] Example 2

[0034] This embodiment provides a method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, comprising the following steps:

[0035] S1. Weigh 1.5 parts by mass of cobalt nitrate hexahydrate, 0.5 parts by mass of iron nitrate nonahydrate, 0.6 parts by mass of nickel nitrate hexahydrate, 0.8 parts by mass of chromium nitrate nonahydrate, 1.5 parts by mass of manganese nitrate hexahydrate and 3.1 parts by mass of hexadecyltrimethylammonium bromide, add them to 100 parts by mass of deionized water, mix well, then add 2.2 parts by mass of urea, stir for 28 minutes, and obtain a mixed solution;

[0036] S2, placing the mixed solution into a polytetrafluoroethylene-lined stainless steel hydrothermal autoclave, hydrothermally reacting at 160° C. for 5 h, and obtaining a precursor powder by centrifugation, washing, and drying;

[0037] S3, heat treating the prepared precursor powder at 950° C. in an air atmosphere for 3 h to obtain a high entropy ceramic;

[0038] S4. Weigh 6 parts by mass of high-entropy ceramics and 3 parts by mass of aluminum phosphate, add them to 100 parts by mass of deionized water, and ultrasonically disperse them for 23 minutes to obtain a suspension; take 16 parts by mass of foam copper and place them in the suspension, immerse them for 18 minutes, take them out, and dry them at 75°C for 11 hours to prepare an outdoor foam copper composite high-entropy ceramic photothermal fresh water evaporator.

[0039] In this embodiment, the thickness of the copper foam is 7 mm and the pore diameter is 50 μm.

[0040] Example 3

[0041] This embodiment provides a method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, comprising the following steps:

[0042] S1. Weigh 1.4 parts by mass of cobalt nitrate hexahydrate, 0.6 parts by mass of iron nitrate nonahydrate, 0.7 parts by mass of nickel nitrate hexahydrate, 0.7 parts by mass of chromium nitrate nonahydrate, 1.4 parts by mass of manganese nitrate hexahydrate and 3.0 parts by mass of hexadecyltrimethylammonium bromide, add them to 100 parts by mass of deionized water, mix well, then add 2.3 parts by mass of urea, stir for 30 minutes, and obtain a mixed solution;

[0043] S2, placing the mixed solution into a polytetrafluoroethylene-lined stainless steel hydrothermal autoclave, hydrothermally reacting at 150° C. for 6 h, and obtaining a precursor powder by centrifugation, washing, and drying;

[0044] S3, heat treating the prepared precursor powder at 1000° C. in an air atmosphere for 3 h to obtain a high entropy ceramic;

[0045] S4. Weigh 10 parts by mass of high-entropy ceramics and 5 parts by mass of aluminum phosphate, add them to 100 parts by mass of deionized water, and ultrasonically disperse them for 25 minutes to obtain a suspension; take 20 parts by mass of foam copper and place them in the suspension, immerse them for 20 minutes, take them out, and dry them at 80°C for 12 hours to prepare an outdoor foam copper composite high-entropy ceramic photothermal fresh water evaporator.

[0046] In this embodiment, the thickness of the copper foam is 8 mm and the pore diameter is 60 μm.

[0047] Example 4

[0048] This embodiment provides a method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, comprising the following steps:

[0049] S1. Weigh 1.6 parts by mass of cobalt nitrate hexahydrate, 0.5 parts by mass of iron nitrate nonahydrate, 0.8 parts by mass of nickel nitrate hexahydrate, 0.8 parts by mass of chromium nitrate nonahydrate, 1.5 parts by mass of manganese nitrate hexahydrate and 3.2 parts by mass of hexadecyl ammonium tribromide, add them to 100 parts by mass of deionized water, mix well, add 2.5 parts by mass of urea, stir for 25 minutes, and obtain a mixed solution;

[0050] S2, placing the mixed solution into a polytetrafluoroethylene-lined stainless steel hydrothermal autoclave, hydrothermally reacting at 160° C. for 5 h, and obtaining a precursor powder by centrifugation, washing, and drying;

[0051] S3, heat treating the prepared precursor powder at 950° C. in an air atmosphere for 2 h to obtain a high entropy ceramic;

[0052] S4. Weigh 8 parts by mass of high-entropy ceramics and 4 parts by mass of aluminum phosphate, add them to 100 parts by mass of deionized water, and ultrasonically disperse them for 30 minutes to obtain a suspension; take 15 parts by mass of foam copper and place them in the suspension, immerse them for 15 minutes, take them out, and dry them at 70°C for 10 hours to prepare an outdoor foam copper composite high-entropy ceramic photothermal fresh water evaporator.

[0053] In this embodiment, the thickness of the copper foam is 10 mm and the pore diameter is 40 μm.

[0054] Performance Testing

[0055] The outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator obtained in Examples 1-4 was tested for water evaporation efficiency. The test conditions / methods were as follows:

[0056] First, the prepared outdoor copper foam composite high-entropy ceramic photothermal fresh water evaporator was cut into evaporator discs with a diameter of 45 mm; then, the discs were floated in a beaker filled with 60 mL of deionized water, and the beaker was placed on an analytical balance with a measurement accuracy of 0.001 g, and the mass was reset to zero; further, a solar simulator was used to irradiate the evaporator discs, and the sunlight intensity was stabilized at 1 KW / m 2 The mass loss was recorded in real time using an analytical balance at a frequency of once per minute. Finally, the obtained time-unit area mass loss data were plotted and the slope was calculated to obtain the water evaporation efficiency.

[0057] The test results are:

[0058] The outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator prepared in Example 1 is 1KW / m 2 The water evaporation efficiency under the sunlight intensity is 1.20 kg·m -2 ·h -1 ;

[0059] Example 2: Outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator at 1KW / m 2 The water evaporation efficiency under sunlight intensity is 1.22 kg·m -2 ·h -1 ;

[0060] Example 3: Outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator at 1KW / m 2 The water evaporation efficiency under sunlight intensity is 1.28 kg·m -2 ·h -1 ;

[0061] Example 4: Outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator at 1KW / m 2 The water evaporation efficiency under sunlight intensity is 1.25 kg·m -2 ·h -1 .

[0062] From the above test data, it can be seen that the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator prepared by the present invention has a power consumption of 1KW / m 2 The water evaporation efficiency under sunlight intensity is 1.20-1.28 kg·m -2 ·h -1 , with high water evaporation efficiency.

Claims

1. A method for preparing an outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, characterized in that: The following steps are involved: S1. Add cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate hexahydrate, and hexadecyltrimethylammonium bromide into deionized water, mix well, then add urea, and stir to obtain a mixed solution; S2, placing the mixed solution prepared in step S1 into a polytetrafluoroethylene-lined stainless steel hydrothermal kettle, performing a hydrothermal reaction at 140-160° C., and obtaining a precursor powder by centrifugation, washing, and drying; S3, heat treating the precursor powder prepared in step S2 at 900-1000° C. in an air atmosphere to obtain a high entropy ceramic; S4, adding the high entropy ceramic and aluminum phosphate prepared in step S3 into deionized water, and obtaining a suspension after ultrasonic dispersion, placing a foam copper in the suspension, wherein the foam copper has a thickness of 5-10 mm and a pore size of 20-60 μm, and immersing for 10-20 min, taking out, and drying to obtain an outdoor foam copper composite high entropy ceramic photothermal fresh water evaporator, wherein the mass ratio of high entropy ceramic, aluminum phosphate, deionized water, and foam copper is (5-10):(3-5):100:(10-20); In step S1, the mass ratio of cobalt nitrate hexahydrate, iron nitrate nonahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate hexahydrate, hexadecyltrimethylammonium bromide, deionized water, and urea is (1.2-1.6):(0.4-0.6):(0.6-0.8):(0.7-0.8):(1.3-1.5):(3.0-3.2):100:(2.0-2.5).

2. The method for preparing the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator according to claim 1, characterized in that: In step S1, stirring is performed for 20 to 30 min to obtain a mixed solution.

3. The method for preparing the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator according to claim 1, characterized in that: In step S2, the hydrothermal reaction time is 4 to 6 h.

4. The method for preparing the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator according to claim 1, characterized in that: In step S3, the heat treatment time is 2 to 3 h.

5. The method for preparing the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator according to claim 1, characterized in that: In step S4, the ultrasonic dispersion time is 20 to 30 min.

6. The method for preparing the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator according to claim 1, characterized in that: In step S4, the drying process is performed at 60-80°C for 10-12 hours.

7. An outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator, characterized in that: The evaporator is prepared by the preparation method of the outdoor copper foam composite high entropy ceramic photothermal fresh water evaporator as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Foamed graphene photo-thermal material and preparation method thereof

    CN109369065A

  • A carbonized rice husk foam photothermal material and its preparation method

    CN109517337B

  • Preparation method and application of seawater desalination material

    CN106277119A

  • High-entropy alloy-based spectral selectivity solar absorption coating and preparation method thereof

    CN112442668A

  • Method for synthesizing spinel type high-entropy oxide material (MCoFeCrMn)3O4 by hydrothermal method

    CN113501709A